ELECTRICAL CONDUCTIVITY OF GRANULED SEMICONDUCTOR THERMOELECTRIC MATERIAL (Ustozlar uchun, 2026)
In the article, the bulk polycrystalline semiconductor silicon and other semiconductor materials that have become unusable appear to be granular. Granulated semiconductor thermoelectric materials based on crushed granules that convert cheap and high-quality thermal energy into electricity using sunlight have been proposed. In the production of granulated thermoelectric material, the preparation of a new type of mono and polycrystalline castings using a solar furnace, as well as the processes associated with charge transfer in the new material obtained are shown.